Pacing profiles of Olympic and IAAF World Championship long-distance runners - Filipas, L.; La Torre, A.; Hanley, B. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to analyze the pacing profiles of Olympic and International Association of Athletics Federations (IAAF) World Championship long-distance finalists, including the relationship with their recent best times. The times for each 1,000-m split were obtained for 394 men and women in 5,000- and 10,000-m finals at 5 championships. Athletes' best times from the previous 32 months were also obtained. Similar pacing profiles were used by athletes grouped by finishing position in 5,000-m races. Women adopted a more even pacing behavior, highlighting a possible sex-based difference over this distance. Pacing behavior over 10,000 m was more similar between men and women compared with over 5,000 m. The main difference between men and women was that in the men's 10,000 m, as in the men's 5,000 m, more athletes were able to follow the leading group until the final stages. There were large or very large correlations between athletes' best times from the previous 32 months and their result; the fastest finishers also ran closer to their previous 32 months' best times. Despite differences in pacing behavior between events, long-distance runners should nonetheless stay close to the front from the beginning to win a medal.